Exergy analysis and economic evaluation of the steam superheat utilization using regenerative turbine in ultra‐supercritical power plants under design/off‐design conditions. Issue 3 (27th June 2017) - Luyao, Zhou; Cheng, Xu; Gang, Xu; Pu, Bai; Yongping, Yang
Abstract: In order to effectively utilize the steam superheat of ultra‐supercritical power plants, a regenerative turbine (RT) system was proposed. In the RT system, a portion of the high‐pressure turbine exhaust steam is sent to an extra turbine termed as RT, and the extracted steam of several regenerative heaters (RHs) would be extracted from the RT instead of the intermediate‐pressure turbine. The superheat degree of related extracted steam would decrease and the exergy destruction of the heat transfer process in RHs would be reduced. Thermodynamic and economic analyses of the RT system in a typical 1000 MW power plant were carried out. The results showed that the heat consumption rate would be reduced as compared to the conventional configuration. When the RT isentropic efficiency is set to 85%, the heat consumption rate of the RT system could decrease by 46.9 kJ/kWh as compared to that of the reference system without RT under design condition. The heat consumption rate decrement will be greater with higher RT isentropic efficiency. Meanwhile, thermodynamic analysis of the RT system under off‐design condition showed that the energy saving effect of the RT system would be decreased when the design conditions are no longer met. The exergy analysis showed that the total exergy destruction decrement of related RHs in the RT system decreases as the load drops down. Moreover, the economic analysis revealed that the net economic benefit of the RT system could reach 0.57 M per year, and would perform economically within a wide range fluctuations of power market conditions. Abstract : A regenerative turbine (RT) system was proposed to use steam superheat. The RT system exhibited a more preferable performance as the power load increased. The RT system was economic in a wide range fluctuations of power market conditions.